Inspiration from the “Biggest Loser”: Social Interactions in a Weight Loss Program - Uetake, Kosuke; Yang, Nathan (Marketing Science, 2020)
We investigate the role of heterogeneous peer effects in encouraging healthy lifestyles. Our analysis revolves around one of the largest and most extensive databases about weight loss that track individual participants’ meeting attendance and progress in a large national weight loss program. The main finding is that, although weight loss among average-performing peers has a negative effect on an individual’s weight loss, the corresponding effect for the top performer among peers is positive. Furthermore, we show that our results are robust to potential issues related to selection into meetings, endogenous peer outcomes, individual unobserved heterogeneity, lagged dependent variables, and contextual effects. Ultimately, these results provide guidance about how the weight loss program should identify role models.